Syntactic ambiguity and its impact on translation strategies from English to Arabic (مجلة البحوث الأكاديمية, 2026)
The study addressed Syntactic ambiguity in the translation of ambiguous sentences with multiple meanings. A mixed-methods approach combining qualitative and quantitative methods was used to ensure the accuracy of the results. A translation test and group discussion were the data collection tools. The sample consisted of 30 fourth-year students majoring in English at the Faculty of Arts, Department of English Language and Literature. The research revealed that the majority of students relied on grammatical rules and logical expectations when translating the test sentences. The results also showed a clear tendency among students to choose the most common translations and avoid alternative meanings, which they generally considered complex and ambiguous. These findings highlight the urgent need for detailed explanations accompanied by practical application for ambiguous sentences, and for developing students' translation skills.